An mHealth Intervention to Improve Young Gay and Bisexual Men's Sexual, Behavioral, and Mental Health in a Structurally Stigmatizing National Context - Leluțiu-Weinberger, Corina; Manu, Monica; Ionescu, Florentina; Dogaru, Bogdan; Kovacs, Tudor; Dorobănțescu, Cristian; Predescu, Mioara; Surace, Anthony; Pachankis, John E (JMIR Publications, 2018)
BackgroundYoung gay and bisexual men (YGBM) in some Eastern European countries, such as Romania, face high stigma and discrimination, including in health care. Increasing HIV transmission is a concern given inadequate prevention, travel to high-prevalence countries, and popularity of sexual networking technologies. ObjectiveThis study aimed to adapt and pilot test, in Romania, a preliminarily efficacious mobile health (mHealth) HIV-prevention intervention, created in the United States, to reduce HIV risk among YGBM. MethodsAfter an intervention formative phase, we enrolled 43 YGBM, mean age 23.2 (SD 3.6) years, who reported condomless sex with a male partner and at least 5 days of heavy drinking in the past 3 months. These YGBM completed up to eight 60-minute text-based counseling sessions grounded in motivational interviewing and cognitive behavioral skills training with trained counselors on a private study mobile platform. We conducted one-group pre-post intervention assessments of sexual (eg, HIV-risk behavior), behavioral (eg, alcohol use), and mental health (eg, depression) outcomes to evaluate the intervention impact. ResultsFrom baseline to follow-up, participants reported significant (1) increases in HIV-related knowledge (mean 4.6 vs mean 4.8; P=.001) and recent HIV testing (mean 2.8 vs mean 3.3; P=.05); (2) reductions in the number of days of heavy alcohol consumption (mean 12.8 vs mean 6.9; P=.005), and (3) increases in the self-efficacy of condom use (mean 3.3 vs mean 4.0; P=.01). Participants reported significant reductions in anxiety (mean 1.4 vs mean 1.0; P=.02) and depression (mean 1.5 vs mean 1.0; P=.003). The intervention yielded high acceptability and feasibility: 86% (38/44) of participants who began the intervention completed the minimum dose of 5 sessions, with an average of 7.1 sessions completed; evaluation interviews indicated that participation was rewarding and an "eye-opener" about HIV risk reduction, healthy identity development, and partner communication. ConclusionsThis first mHealth HIV risk-reduction pilot intervention for YGBM in Eastern Europe indicates preliminary efficacy and strong acceptability and feasibility. This mobile prevention tool lends itself to broad dissemination across various similar settings pending future efficacy testing in a large trial, especially in contexts where stigma keeps YGBM out of reach of affirmative health interventions.